The application and progress of tissue engineering and biomaterial scaffolds for total auricular reconstruction in microtia - Huang, Yeqian; Zhao, Hanxing; Wang, Yixi; Bi, Siwei; Zhou, Kai; Li, Hairui; Zhou, Changchun; Wang, Yudong; Wu, Wenqing; Peng, Bo; Tang, Jun; Pan, Bo; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Microtia is a congenital deformity of the ear with an incidence of about 0.8-4.2 per 10,000 births. Total auricular reconstruction is the preferred treatment of microtia at present, and one of the core technologies is the preparation of cartilage scaffolds. Autologous costal cartilage is recognized as the best material source for constructing scaffold platforms, however, costal cartilage harvest can lead to donor-site injuries such as pneumothorax, postoperative pain, chest wall scar and deformity. Therefore, with the need of alternative to autologous cartilage, in vitro and in vivo studies of biomaterial scaffolds and cartilage tissue engineering have gradually become novel research hot points in auricular reconstruction research. Tissue-engineered cartilage possesses obvious advantages including non-rejection, minimally invasive or non-invasive, the potential of large-scale production to ensure sufficient donors and controllable morphology. Exploration and advancements of tissue-engineered cartilaginous framework are also emerging in aspects including three-dimensional biomaterial scaffolds, acquisition of seed cells and chondrocytes, 3D printing techniques, inducing factors for chondrogenesis and so on, which has greatly promoted the research process of biomaterial substitute. This review discussed the development, current application and research progress of cartilage tissue engineering in auricular reconstruction, particularly the usage and creation of biomaterial scaffolds. The development and selection of various types of seed cells and inducing factors to stimulate chondrogenic differentiation in auricular cartilage were also highlighted. There are still confronted challenges before the clinical application become widely available for patients, and its long-term effect remains to be evaluated. We hope to provide guidance for future research directions of biomaterials as an alternative to autologous cartilage in ear reconstruction, and finally benefit to the transformation and clinical application of cartilage tissue engineering and biomaterials in microtia treatment.